Optimalisasi Strategi Pemasaran Digital bagi UMKM melalui Pelatihan Kewirausahaan Berbasis Teknologi dalam Mendukung Pertumbuhan Ekonomi Daerah Kabupaten Pringsewu - Ni Putu Widhia Rahayu; Tina Miniawati Barusman; Haninun Haninun; Imanuriea Anisa Putri; Luke Suciyati Amna (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2026)
The development of digital technology provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve their competitiveness through the implementation of digital marketing strategies. However, many MSME actors in Pringsewu Regency still face limitations in utilizing technology, managing digital platforms, and implementing internet-based marketing strategies. This activity aims to optimize the capabilities of MSME actors through technology-based entrepreneurship training to improve digital marketing effectiveness and support regional economic growth. The implementation methods include identifying MSME needs, providing training on digital platform utilization, developing social media promotion strategies, creating creative digital content, and assisting participants in implementing digital marketing practices. The results indicate an improvement in participants’ knowledge and skills in utilizing digital technology to expand market reach, increase customer engagement, and develop business innovations. The implementation of digital marketing strategies is expected to strengthen MSME sustainability and contribute to improving the economic growth of communities in Pringsewu Regency.